2013
DOI: 10.1097/sla.0b013e31827e9289
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Possibility of a Cure in Patients With Colorectal Peritoneal Carcinomatosis Amenable to Complete Cytoreductive Surgery and Intraperitoneal Chemotherapy?

Abstract: The cure rate (16%) after complete CRS of colorectal peritoneal carcinomatosis, followed by IPC, in selected patients is close to that obtained after resection of colorectal liver metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
100
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(108 citation statements)
references
References 45 publications
6
100
0
2
Order By: Relevance
“…Elias et al have demonstrated a cure rate (16%) after complete CRS of colorectal peritoneal carcinomatosis, followed by intraperitoneal chemotherapy in selected patients is close to that obtained after resection of colorectal liver metastases [1].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Elias et al have demonstrated a cure rate (16%) after complete CRS of colorectal peritoneal carcinomatosis, followed by intraperitoneal chemotherapy in selected patients is close to that obtained after resection of colorectal liver metastases [1].…”
Section: Discussionmentioning
confidence: 99%
“…Cytoreductive surgery and HIPEC provides an important chance of long term survival in patients with peritoneal spread of colorectal cancer [1,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some suggest that 20 is a limit over which the surgical approach should be excluded [71]. Yet even if the Uppsala group report that treatment for high-volume peritoneal disease (PCI >20) seldom results in long-term survival [72], in their multivariate analysis Goéré et al found as the only independent factor predicting cure a PCI of 10 or less (73): the median PCI in long-term survivors was 4, a value we rarely find in our clinical practice.…”
Section: Proactive Management Of Peritoneal Metastases From Colorectamentioning
confidence: 98%
“…Cette histoire naturelle n'est plus vraie de nos jours grâce à la chirurgie de cytoréduction associée à la chimiothérapie hyperthermique intrapéritonéale peropé-ratoire (CHIP). Ce traitement relativement récent, quand il est réalisable, est recommandé dans la prise en charge de la carcinose péritonéale d'origine colorectale [2][3][4][5][6].…”
Section: Introductionunclassified